MIGRACIÓN Y HABILIDADES SOCIALES DE LOS ESTUDIANTES DE LA UNIDAD EDUCATIVA INTERCULTURAL BILINGÜE “MONSEÑOR LEONIDAS PROAÑO”, RIOBAMBA, PERÍODO OCTUBRE 2018 – MARZO 2019 - Barahona Guamán, Diego Armando (2019)
The objective of this research was to determine the correlation of the migratory situation with the social skills of the students of the Ninth year of Basic General Education at the "Monseñor Leonidas Proaño" Intercultural Bilingual Educational Unit in Riobamba – Chimborazo; period October 2018 - March 2019. Migration is considered a movement of several people from their usual place of residence to one in which they must stay for a period in order to satisfy their needs. Social skills are a set of behaviors that allow a person to develop in an individual or interpersonal context expressing feelings, attitudes, desires, opinions or rights in an appropriate way to the situation. Methodologically, we have worked with a non-experimental research design. The research was of bibliographic, field and transversal type; then being the level of the research descriptive and correlational. The sample was of a non-probabilistic and intentional type on the part of the researchers and consists in 71 students of basic education ninth grade basic education. For the collection of data, the survey as a technique and the questionnaire as an instrument were used in terms of migration; while for social skills the psychometric test was used as a technique and the social skills scale of Elena Gismero as an instrument. From which it could be shown that there is a correlation between migration and social skills, that is, migrant students have greater difficulties in establishing an adequate interaction with other people, unlike students who have not undergone migration processes.